Penta Helix Collaboration in Increasing Regional Tourism Competitiveness of Bandung City - Idah Wahidah; Diki Suherman (Jurnal Manajemen Pelayanan Publik, 2022)
Bandung City tourism is a potential sector that can be relied upon because it contributes greatly to regional income, but there are problems, namely accessibility due to city congestion which results in slow mobility, and dependence on the local government of Bandung City is another obstacle. This study aims to analyze the penta helix collaboration in increasing the competitiveness of Bandung City tourism, using a qualitative method through a descriptive approach. The method used is qualitative through a descriptive approach. Based on the results of research, Bandung City Tourism has its own uniqueness, especially tourism through the development of various innovations, through active collaboration between elements of the government, businessmen, communities, academics and the media as an effort to increase the competitiveness of regional tourism. Through the development of tourist destinations in increasing the tourism attractiveness of the Bandung City area, it has implications for improving the welfare of the community through local economic growth.